Development of FitSchedule: An Offline Workout Planner Application Using Flutter, Cubit, and SQLite - Sri Sugiarti; Efa Mutiara Sari; Siti Rahmah Azzahra (Jurnal Publikasi Ilmu Komputer Terapan, 2026)
The rapid advancement of mobile technology has significantly transformed the way people manage health and fitness activities. Although numerous fitness applications are available on mobile platforms, many rely on cloud services, require user authentication, or depend on a stable internet connection, limiting accessibility for users who prefer lightweight offline solutions. This study aims to develop FitSchedule, an Android-based workout planner application that enables users to organize workout programs, manage exercise lists, record workout history, and monitor training progress without requiring internet connectivity. The application was developed using the Waterfall software development methodology, which consists of requirement analysis, system design, implementation, testing, and maintenance. Flutter was employed as the cross-platform development framework with Dart as the programming language. The application adopted the Cubit architecture from the Flutter BLoC library to separate business logic from the presentation layer, thereby improving maintainability and scalability. SQLite was utilized as the local database to ensure persistent offline data storage. The primary features include workout program management, exercise management, active workout sessions, workout history recording, and workout statistics visualization. on was conducted using Black Box Testing to evaluate all major application features. The testing results demonstrated that every functional requirement operated successfully without significant defects. The integration of Flutter, Cubit, and SQLite produced an application with responsive performance, modular architecture, and reliable offline capability. The developed application provides an effective solution for individuals seeking a simple and practical workout planner while also serving as a reference for implementing Flutter-based mobile applications using Cubit state management and local database technology. on was conducted using Black Box Testing to evaluate all major application features. The testing results demonstrated that every functional requirement operated successfully without significant defects. The integration of Flutter, Cubit, and SQLite produced an application with responsive performance, modular architecture, and reliable offline capability. The developed application provides an effective solution for individuals seeking a simple and practical workout planner while also serving as a reference for implementing Flutter-based mobile applications using Cubit state management and local database technology.